Research on Zakat Governance - Mimma Maripatul Uula (Islamic Social Finance, 2022)
This study aims to see the development of research zakat governance around the world published by journals with that theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme of Islamic bank efficiency originating from the Dimension database for 2007-2023. Then, the data was processed and analyzed using the VosViewer application with the aim of knowing the research development bibliometric map zakat governance in this world. The results of the study found that author mapping based on cluster density shows that the authors do the most publications with the theme Zakat Governance namely Nikmatul Atiya, Eko Fajar Cahyono, and Sri Herianingrum. Then, the most author affiliations are Al Ain University and Aligarh Muslim University. Next Zakat Governance based on the bibliometric keyword mapping, there are 4 clusters with the most used words being Accounting, Distribution, Good governance and Government.